2012
DOI: 10.1007/s00234-012-1025-9
|View full text |Cite
|
Sign up to set email alerts
|

Carotid plaque signal differences among four kinds of T1-weighted magnetic resonance imaging techniques: A histopathological correlation study

Abstract: Among T1W MR imaging techniques, non-gated SE images can more accurately characterize intraplaque components in patients who underwent CEA when compared with cardiac-gated BB-FSE, MPRAGE, and SI-MRA images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 19 publications
1
40
0
Order By: Relevance
“…The sensitivity of the high signal intensity halo for detecting carotid IPH was 91%. Saito et al (16) reported that carotid IPH signal differences between spine echo, MPRAGE, and TOF by 1.5-T MR show similar accuracies for characterizing plaque components using histopathological information. However, Ota et al (8) reported the diagnostic performance of three T1-weighted MR sequences, 2D fast spin-echo, 3D TOF, and 3D MPRAGE, on carotid IPH imaging, using histologic analysis as the standard of reference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of the high signal intensity halo for detecting carotid IPH was 91%. Saito et al (16) reported that carotid IPH signal differences between spine echo, MPRAGE, and TOF by 1.5-T MR show similar accuracies for characterizing plaque components using histopathological information. However, Ota et al (8) reported the diagnostic performance of three T1-weighted MR sequences, 2D fast spin-echo, 3D TOF, and 3D MPRAGE, on carotid IPH imaging, using histologic analysis as the standard of reference.…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not include patients who had received carotid endarterectomy, therefore histologic results were not available. Previous studies have demonstrated the diagnostic usefulness of MPRAGE sequence for IPH detection (8,16). Second, a relatively small number of patients were examined, and it was a retrospective design.…”
Section: Discussionmentioning
confidence: 99%
“…Various imaging protocols and techniques have been applied in MR plaque imaging, and the results in previous reports have varied. 5,7,[10][11][12][13]16,17 Of these protocols, an electrocardiographgated 2D fast SE technique with a black-blood method is commonly applied. 10,16 However, this method is generally complicated and time-consuming and can obtain only a few sections of imaging.…”
Section: Discussionmentioning
confidence: 99%
“…In this method, moreover, the heart rate of patients forces the TR to be inappropriate, resulting in deterioration of image contrast. 6,7,17 A magnetization-prepared rapid acquisition of gradient echo technique has also been widely used. 18,19 In this technique, however, an inversion pulse for suppressing the blood signal is nonspecific and can attenuate the signal of the lipid/necrotic component that has T1 relaxation times similar to those of blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation